(untitled) (CIPEEX, 2022)
OBJECTIVE: TO UNDERSTAND THE BENEFITS AND DIFFICULTIES OF TELEMEDICINE AS AN ALTERNATIVE IN HEALTHCARE ACCESS. METHODS: INTEGRATIVE REVIEW OF 19 ARTICLES WITH BIBLIOGRAPHIC SEARCH IN THE NATIONAL LIBRARY OF MEDICINE AND NATIONAL INSTITUTES OF HEALTH (PUBMED), LATIN AMERICAN AND CARIBBEAN LITERATURE ON HEALTH SCIENCES (LILACS) AND COORDINATION OF SUPERIOR LEVEL STAFF IMPROVEMENT (CAPES). DESCRIPTORS USED: €ŒTELEMEDICINE€, €ŒHEALTHCARE ACCESS€, €ŒPRIMARY HEALTH CARE€ AND €ŒHEALTH CARE SURVEYS€. INCLUSION CRITERIA: ARTICLES PUBLISHED BETWEEN 2018 AND 2022 THAT ANSWERED THE GUIDING QUESTION: WHAT ARE THE BENEFITS AND DIFFICULTIES OF TELEMEDICINE AS AN ALTERNATIVE IN ACCESSING HEALTHCARE? RESULTS: MAIN BENEFITS: EXPANSION OF HEALTH ACCESS AND GUARANTEE OF LONGITUDINALITY AND RESOLUTION. MAIN DIFFICULTIES: SCARCE HUMAN AND STRUCTURAL RESOURCES, LOSS OF CONTACT BETWEEN DOCTOR AND PATIENT AND DIFFICULTY IN DEALING WITH TECHNOLOGICAL RESOURCES. CONCLUSION: THE USE OF TELEMEDICINE AS A TOOL TO DISSEMINATE ACCESS TO HEALTH IS VALID. HOWEVER, COLLABORATION AND TRAINING OF USERS AND HEALTH PROFESSIONALS ARE NECESSARY. IT IS ESSENTIAL TO DEVELOP OTHER STUDIES RELATED TO THE POSSIBILITIES THAT THIS MODALITY BRINGS. &NBSP; KEY WORDS: TELEMEDICINE, HEALTHCARE ACCESS, PRIMARY HEALTH CARE, HEALTH CARE SURVEYS